2020
DOI: 10.3389/fimmu.2020.01543
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Complement Components and Vitamin D and the Physical Activities of Daily Living Among a Longevous Population in Hainan, China

Abstract: Background: Vitamin D and complement components shared some common pathophysiological pathways in the musculoskeletal system, circulation, and metabolism, which were linked to physical function. It is hypothesized that serum complement components may interact with vitamin D in respect of the physical activities of daily living (PADLs). Objective: To investigate if serum complement components 3 (C3), complement components 4 (C4), and 25-hydroxyvitamin D [25(OH)D] associate with PADLs, and to examine whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Therefore, the CHCCS provides a good model for investigating aging and longevity in community-dwelling centenarians. Our previous work suggested that the serum 25(OH)D level might be associated with activities of daily living, functional dependence, and symptoms of depression at baseline in participants in the CHCCS [ 27 , 28 , 29 ]. In the present study, we further demonstrated that not only the 25(OH)D level but also the PTH and β-CTX levels were associated with all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the CHCCS provides a good model for investigating aging and longevity in community-dwelling centenarians. Our previous work suggested that the serum 25(OH)D level might be associated with activities of daily living, functional dependence, and symptoms of depression at baseline in participants in the CHCCS [ 27 , 28 , 29 ]. In the present study, we further demonstrated that not only the 25(OH)D level but also the PTH and β-CTX levels were associated with all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Last childbearing age (LCA) referred to the age at which the woman gave birth to the last live offspring. Barthel Index (BI) was used to evaluate the activities of daily living (ADL); its validity and reliability in Chinese older individuals have been well established ( 26 ). BI consists of 10 items that measure a person’s daily activities: grooming, feeding, dressing, bathing, toilet use, transfer from bed to chair, walking, stair climbing, bowel continence, and urinary continence.…”
Section: Methodsmentioning
confidence: 99%
“…According to earlier research, VitD boosts the release of some anti-inflammatory cytokines while decreasing the release of some pro-inflammatory cytokines [ 96 , 97 ]. Thus, there may be conflicting effect between VitD and the levels of C3 and C4 in immunological and inflammatory pathways [ 98 ].…”
Section: The Relationship Between Vitamin D Levels and Complement Act...mentioning
confidence: 99%